2013
DOI: 10.1007/s11102-013-0517-x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary incidentalomas

Abstract: Current experience from a multidisciplinary pituitary center is presented, with indications for treatment and longitudinal care of these challenging patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 40 publications
4
23
0
1
Order By: Relevance
“…11,12 In fact, most series of incidentally discovered pituitary adenomas include patients who were diagnosed after imaging for other complaints such as trauma, sinus disease, and headache. 3 A recent 16-year study showed a 3-fold increased incidence of pituitary adenomas, mostly seen during the last 8 years of the study. This was found to be due to an increased incidence of incidental pituitary lesions seen on neuroradiological imaging, rather than an increase in symptomatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 In fact, most series of incidentally discovered pituitary adenomas include patients who were diagnosed after imaging for other complaints such as trauma, sinus disease, and headache. 3 A recent 16-year study showed a 3-fold increased incidence of pituitary adenomas, mostly seen during the last 8 years of the study. This was found to be due to an increased incidence of incidental pituitary lesions seen on neuroradiological imaging, rather than an increase in symptomatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a growing and important population of patients with pituitary tumors who present for medical or surgical treatment have these incidentalomas. 3 For example, the overall prevalence of pituitary lesions on autopsy in 1 large series of nearly 19,000 cases was 10.7%. 4 On computed tomography (CT) and magnetic resonance imaging (MRI) series, the reported prevalence is as high as 20% and 38%, respectively.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, an increasing number of incidentalomas in endocrine organs is found on imaging studies (Golden et al 2009, Molitch 2009, Scangas & Laws 2014. In patients who are not from known MEN1 families, apparently sporadically occurring tumors might actually be caused by a not yet identified MEN1 mutation.…”
Section: Genetic Testing Of Men1 In Index Casesmentioning
confidence: 99%
“…Intensive radiological screening appears to reveal pituitary incidentalomas, significance of which is still largely unknown (Dekkers et al 2006, de Laat et al 2015. Incidental microadenomas are reported in up to 10% of normal population (Molitch 2009, Freda et al 2011, Scangas & Laws 2014. In a recent study, the impact of screening for PIT among MEN1 patients was evaluated.…”
Section: :10mentioning
confidence: 99%